ВЗАИМОДЕЙТСВИЕ СИСТЕМЫ ФОРМАЛИН-УРОТРОПИН-СУЛЬФАТ МЕДИ (Scientific journal of the Fergana State University, 2023)
Annotation. One of the main directions of increasing crop yields is to provide agriculture with mineral fertilizers, plant growth stimulants and fungicides and pesticides. For pre-sowing treatment of seeds, they must contain several active substances. In this article, the physicochemical properties of the formalin-urotropin-copper sulfate system were studied. Based on the data obtained, a solubility diagram was constructed, identified by physico-chemical methods.